Individualized risk estimation for postoperative morbidity after hepatectomy: the Humanitas score. Issue 10 (October 2017) - Donadon, Matteo; Fontana, Andrea; Palmisano, Angela; Viganò, Luca; Procopio, Fabio; Cimino, Matteo; Del Fabbro, Daniele; Torzilli, Guido
Abstract: Background: Estimation of postoperative morbidity after hepatectomy remains challenging. The aim of this prospective study was to develop a surgical score to predict an individual risk of post-hepatectomy complications. Methods: All consecutive patients scheduled for hepatectomy from February 2012 to September 2015 were included and randomly assigned into a derivation or validation cohort. We developed a score based on preoperative variables, and we tested them using multivariate analyses. Odds-ratio (OR) values were used to build the score. Results: 340 patients were included, 240 in the derivation and 100 in the validation cohort. Multivariate analysis showed that major hepatectomy (OR = 1.62; 95% CI 1.39–3.51), liver stiffness ≥9.7 kPa (OR = 2.46; 95% CI 1.16–5.28), BILCHE score (combination of serum bilirubin and cholinesterase) ≥2 (OR = 2.76; 95% CI 0.82–4.28) and esophageal varices (OR = 1.59; 95% CI 1.51–3.61) were independent complications predictors. A 10-point scoring system was introduced. Patients with a score ≤4 did not experience complications, whereas patients with ≥7 points experienced up to 54% of complications (P < 0.001). Conclusions: A new, easy and clinically reliable surgical score based on the liver stiffness, BILCHE score, type of hepatectomy, and presence of varices may be used to predict post-hepatectomy morbidity. Clinical trial number: NCT02454686 (https://www.clinicaltrials.gov/ ).